2013
DOI: 10.1103/physrevb.87.085127
|View full text |Cite
|
Sign up to set email alerts
|

Long transient dynamics in the Anderson-Holstein model out of equilibrium

Abstract: We calculate the time-dependent nonequilibrium current through a single-level quantum dot strongly coupled to a vibrational mode. The nonequilibrium real-time dynamics caused by an instantaneous coupling of the leads to the quantum dot is discussed using an approximate method. The approach, which is specially designed for the strong polaronic regime, is based on the so-called polaron tunneling approximation. Considering different initial dot occupations, we show that a common steady state is reached after time… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
89
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(99 citation statements)
references
References 47 publications
10
89
0
Order By: Relevance
“…Recent calculations, based on numerically exact methods such as diagrammatic quantum Monte Carlo (diagMC) [28], have indicated that for strong electron-phonon coupling there exists a regime in which different initial conditions lead to different transport properties at short times. In a subsequent work [29] it was demonstrated that this apparent bistability actually corresponds to a long transient dynamics leading to blockingdeblocking events associated with the polaron dynamics. More recent work [30] has confirmed the analysis and also explored the effect of including the dot-leads Coulomb repulsion.…”
Section: Introductionmentioning
confidence: 93%
“…Recent calculations, based on numerically exact methods such as diagrammatic quantum Monte Carlo (diagMC) [28], have indicated that for strong electron-phonon coupling there exists a regime in which different initial conditions lead to different transport properties at short times. In a subsequent work [29] it was demonstrated that this apparent bistability actually corresponds to a long transient dynamics leading to blockingdeblocking events associated with the polaron dynamics. More recent work [30] has confirmed the analysis and also explored the effect of including the dot-leads Coulomb repulsion.…”
Section: Introductionmentioning
confidence: 93%
“…The celebrated Anderson-Holstein model, with a single electronic orbital coupled to a local phonon mode, exposes an intricate interplay between the electronic and nuclear degrees of freedom. The model has been extensively studied to reveal the behavior of the current and its fluctuations in different regimes of electron-phonon coupling, see for example [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] . An extension of the Anderson-Holstein model with a secondary phonon bath was examined in many studies, see e.g.…”
Section: Introductionmentioning
confidence: 99%
“…However, recent calculations of the nonequilibrium current based on time-dependent density functional theory seem to indicate that at long times the system reaches a dynamical state characterized by correlation-induced current oscillations 2 . Similarly, questions regarding hysteresis, bistability and the dependence of the steady-state current on the initial occupation have been raised in the context of inelastic transport through nanoscale quantum dots [3][4][5][6][7][8][9][10][11] . Addressing the issue of a unique steady-state is a challenging task for theory, as systems exhibiting bistability involve strong electron-electron or electron-phonon correlations.…”
Section: Introductionmentioning
confidence: 99%